Badania i rozwój – jak zwiększyć polską innowacyjność poprzez politykę podatkową? - Bronżewska, Katarzyna; Majdowski, Filip (Kwartalnik Prawa Podatkowego, 2015)
The article discusses tax policy with respect to research and development (R&D) activities, presents the status quo of Polish tax incentives in this area as well as the proposed legislative amendments from spring 2015. It also analyzes selected Dutch and British solutions (patent boxes) and the ongoing work by the OECD and EU that might indicate the future Polish approach to taxation of R&D activities.